2019
DOI: 10.1001/jamapsychiatry.2019.0951
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy and Acceptability of Pharmacological, Psychotherapeutic, and Combination Treatments in Adults With Posttraumatic Stress Disorder

Abstract: IMPORTANCE Posttraumatic stress disorder (PTSD) is a prevalent mental disorder, with a high risk of chronicity, comorbidity, and functional impairment; PTSD is complicated to treat, and the debate on the best treatment approach is ongoing. OBJECTIVE To examine comparative outcomes and acceptability of psychotherapeutic and pharmacological treatments and their combinations in adults with PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(70 citation statements)
references
References 86 publications
3
66
0
1
Order By: Relevance
“…Overall, among enrolled participants, all of whom previously failed to tolerate or respond to other medications and/or therapies, there was a 7.6% dropout rate in the treatment period across the six MDMA phase 2 studies. This falls close to the lower range cited in the literature for other pharmacotherapies and trauma-focused psychotherapies (0-79%) (Imel et al 2013;Lee et al 2016;Merz et al 2019) and below an average reported dropout rate of 29% (Lee et al 2016). Additionally, 94% of participants reported the opinion that more MDMA sessions would be helpful.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Overall, among enrolled participants, all of whom previously failed to tolerate or respond to other medications and/or therapies, there was a 7.6% dropout rate in the treatment period across the six MDMA phase 2 studies. This falls close to the lower range cited in the literature for other pharmacotherapies and trauma-focused psychotherapies (0-79%) (Imel et al 2013;Lee et al 2016;Merz et al 2019) and below an average reported dropout rate of 29% (Lee et al 2016). Additionally, 94% of participants reported the opinion that more MDMA sessions would be helpful.…”
Section: Discussionsupporting
confidence: 75%
“…Pharmacological treatments for PTSD typically require daily administration of medications, and symptoms often return when patients discontinue their medications (Batelaan et al 2017). Psychotherapies for PTSD, compared to pharmacotherapies, have greater effects with more enduring benefits (Kline et al 2018;Lee et al 2016;Merz et al 2019) and typically have lower dropout rates. This is particularly true of trauma-focused therapies, which are considered first-line treatment for PTSD, that require participants to engage with trauma-related thoughts, feelings, and responses (Lee et al 2016;Steenkamp et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These findings partly concur with Merz and colleagues, who recently showed that psychotherapeutic treatments are superior to pharmacological treatments for adults with PTSD at last follow-up but not at end of treatment, reaffirming the view that pharmacological therapy should not be used as first-line treatment for PTSD [145]. Our findings endorse this view and extend the relevance of international guideline recommendations that favour using TF-CBT and EMDR as first-line treatment for PTSD symptoms to those with histories of complex trauma.…”
Section: Plos Medicinesupporting
confidence: 82%
“…Current guidelines for PTSD suggest psychotherapy as first-line treatment over pharmacological monotherapies, namely the SSRIs sertraline and paroxetine, the only two Federal Drug Administration (FDA)-approved medications for PTSD [52]. The effect size for both exposure therapy and CBT, two popular psychotherapeutic options, was about 8.0 when compared to waitlist or supportive counseling [53].…”
Section: Ptsdmentioning
confidence: 99%